Literature Review of Public Relations Management Strategies in Enhancing Student Enrollment in Islamic Educational Institutions - Marya Ulfa; Oki Dermawan; Muhammad Anas Maarif (re-JIEM (Research Journal of Islamic Education Management), 2026)
The escalating competitive dynamics and shifting public preferences in the era of digital disruption necessitate Islamic educational institutions to reconstruct their public communication strategies. Numerous madrasas and Islamic schools are experiencing stagnant student enrollment due to conventional and fragmented public relations approaches. This situation highlights the urgency to formulate strategic communication guidelines, enabling institutions to overcome enrollment stagnation. This research aims to synthesize Public Relations (PR) management strategies proven effective in boosting the interest of prospective students. Employing the Kitchenham model of Systematic Literature Review (SLR), 10 published empirical journal articles (2021-2025) were collected and extracted. Based on thematic analysis, four primary strategic pillars were identified: (1) optimizing digital-based PR management (Cyber Public Relations) to facilitate interactive communication; (2) strategic planning involving stakeholder participation (committees, parents, community); (3) synergizing direct outreach with partnership networks; and (4) strengthening branding through service differentiation and religious values. The findings assert that increasing student enrollment heavily relies on transforming the PR role from a mere technical implementer to a strategic managerial function capable of adapting to technological innovations without compromising the institution's Islamic identity.